Building locally relevant models for Universal Health Coverage and its implications for Health Information Systems: Some Reflections from India - Sahay, Sundeep; Sundararaman, T; Mukherjee, Arunima S (Journal of Health Informatics in Africa, 2015)
The global health agenda is placing Universal Health Coverage (UHC) as a foundational element of future health reforms, However, a missing link in these discussions is the implications that UHC will have on the supporting Health Information Systems, and how can countries get ready with effective HIS. Also, as calls for country specific research on UHC gains prominence, it is important HIS related research gets integrated in this agenda. This paper speaks to this agenda, and describes an ongoing pilot study from the state of Punjab in India with a focus on the implications of UHC models on HIS. Five key implications on HIS are identified: Expanding basket of services; Population basing of services; Ensuring continuity of care; Resource allocation choices; Monitoring financial protection and costs of care